Utilization of Cloud Technology Applications for Efficient Office Administration among Secretaries in Rivers State Universities - Ikepu Christian Oghenerukevwe; NumbaraBari E Kayii (International Journal of Information Systems and Informatics, 2023)
The study aimed at assessing the utilization of cloud technology applications for efficient office administration among secretaries at Rivers State universities. Three research questions were posed and answered, while three corresponding hypotheses were formulated and tested at 0.05 level of significance. The research design adopted for this study is an analytic-descriptive design. The population for this study consisted of all 91 secretaries at Rivers State universities. The instrument used for data collection was the "Cloud Technology Applications Questionnaire (CTAQ)". The CTAQ was composed of 30 items graded on a four-point scale. The instrument was subjected to content and validity checks by three experts, and a reliability test was conducted using Cronbach's alpha, which gave an overall coefficient of stability of 0.75. Data gathered for research questions was analyzed using mean and standard deviation, and the formulated null hypotheses were tested with a t-test at 0.05 alpha. The findings revealed, among other things, that secretaries in Rivers State universities used platform as a service (PaaS) for office administration to a lesser extent than they used software as a service and communication as a service (CaaS) for office administration. Also, findings revealed that there is no statistically significant difference in the mean ratings of university secretaries at Rivers State University and Ignatius Ajuru University of Education for their use of platform as a service (PaaS), software as a service (SaaS), and communication as a service (CaaS) for office administration. Based on the findings, it was recommended, among others, that universities should create a digital environment to increase and support the use of cloud computing services or applications among employees.